Application of the Minority Stress Theory: Understanding the Mental Health of Undocumented Latinx Immigrants - Valentín‐Cortés, Mislael; Benavides, Quetzabel; Bryce, Richard; Rabinowitz, Ellen; Rion, Raymond; Lopez, William D.; Fleming, Paul J. (American journal of community psychology, 2020)
This paper applies the Minority Stress framework to data collected from an ongoing community‐based participatory research project with health and social service agencies in Southeast Michigan. We examine the stressors and coping strategies employed by undocumented Latinx immigrants and their families to manage immigration‐related stress. We conducted in‐depth interviews with 23 immigrant clients at Federally Qualified Health Care Centers (FQHC) in Southeast Michigan and 28 in‐depth interviews with staff at two FQHC's and a non‐profit agency serving immigrants. Findings suggest that immigrants face heightened anxiety and adverse mental health outcomes because of unique minority identity‐related stressors created by a growing anti‐immigrant social environment. Chronic stress experienced stems from restrictive immigration policies, anti‐immigrant rhetoric in the media and by political leaders, fear of deportation, discriminatory events, concealment, and internalized anti‐immigrant sentiment. Though identity can be an important effect modifier in the stress process, social isolation in the immigrant community has heightened the impact of stress and impeded coping strategies. These stressors have resulted in distrust in community resources, uncertainty about future health benefits, delayed medical care, and adverse mental health outcomes. Findings provide a framework for understanding the unique stressors experienced by immigrants and strategies for interventions by social service agencies. Highlights Mental health disparities affecting undocumented Latinx immigrants. Novel application of Minority Stress Theory to a marginalized population. Effect of current sociopolitical climate on Latinx immigrants and their families. Stressors at multiple levels affecting undocumented Latinx immigrant populations and their families. Community‐based participatory approaches to public health research and practice.